Housing Insecurity Among Patients With Cancer. (21st September 2022) - Fan, Qinjin; Keene, Danya E; Banegas, Matthew P; Gehlert, Sarah; Gottlieb, Laura M; Yabroff, K Robin; Pollack, Craig E
Abstract: Social determinants of health are the economic and environmental conditions under which people are born, live, work, and age that affect health. These structural factors underlie many of the long-standing inequities in cancer care and outcomes that vary by geography, socioeconomic status, and race and ethnicity in the United States. Housing insecurity, including lack of safe, affordable, and stable housing, is a key social determinant of health that can influence—and be influenced by—cancer care across the continuum, from prevention to screening, diagnosis, treatment, and survivorship. During 2021, the National Cancer Policy Forum of the National Academies of Science, Engineering, and Medicine sponsored a series of webinars addressing social determinants of health, including food, housing, and transportation insecurity, and their associations with cancer care and patient outcomes. This dissemination commentary summarizes the formal presentations and panel discussions from the webinar devoted to housing insecurity. It provides an overview of housing insecurity and health care across the cancer control continuum, describes health system interventions to minimize the impact of housing insecurity on patients with cancer, and identifies challenges and opportunities for addressing housing insecurity and improving health equity. Systematically identifying and addressing housing insecurity to ensure equitable access to cancer care and reduce health disparities will require ongoing investment at the practice, systems, and broader policy levels.